TP53 mutations in cell-free DNA as early markers of therapeutic response in platinum-resistant relapsed ovarian cancer (PROC): a prospective translational analysis of the phase II GANNET53 clinical trial. (1st November 2019) - Vanderstichele, A; Concin, N; Busschaert, P; Braicu, I; Combe, P; Ray-Coquard, I; Joly, F; Harter, P; Wimberger, P; Selle, F; Ignatov, A; Schmalfeldt, B; et al.
Abstract : Introduction/Background: Detecting tumor-specific genetic alterations in cell-free DNA (cfDNA) obtained from cancer patients allows for a quantification of the tumoral fraction, i.e. the circulating tumor DNA (ctDNA). Previous studies in metastatic cancer patients showed that early changes of this fraction during therapy are indicative of therapeutic response. We tested this hypothesis on cfDNA samples collected in the GANNET53 clinical trial (FP7, funded by the European Commission, grant no 602602). Methodology: Patients with high-grade serous/endometrioid and/or undifferentiated PROC were recruited for treatment with weekly paclitaxel with or without Hsp90-inhibitor ganetespib. Archival biopsy samples were used for tumor TP53 genotyping. CfDNA was prospectively collected prior to treatment at baseline (cycle 1 day 1, C1D1), 24 hours later (cycle 1 day 2, C1D2) and after 4 and 8 weeks, at day 1 of cycle 2 (C2D1) and 3 (C3D1) respectively. Targeted TP53 resequencing was performed on cfDNA and allelic frequencies of the known TP53 variant (TP53 VAF) were quantified and correlated with clinical outcome. Results: For 125 of the 133 randomized patients, at least 1 C1D1 cfDNA sample was available. For 119 tumor samples, TP53 genotyping was successful and identified deleterious TP53 mutations in 106 patients (89.1%). The median ctDNA level was 1.82% (IQR:0.17–8.34%) at C1D1 which decreased significantly after 4–8 weeks of therapy. Overall, ctDNA was detectable in 64.6% (64/99) of baseline samples. Baseline CA125 did not differ between cases with and without detectable ctDNA at C1D1. Detection of ctDNA at C1D1 (HR 2.3; 95%CI:1.4–3.9), C1D2 (HR 2.2; 95%CI:1.3–3.9) and C2D1 (HR 2.8; 95%CI:1.6–4.9) predicted a worse overall survival. A subgroup of patients for whom TP53 ctDNA was undetectable at C2D1 or C3D1 (14/64) had a high overall response rate of 64.2%. Conclusion: Quantification of TP53 mutations in cfDNA of PROC patients has prognostic value at baseline. Favorable early changes during treatment may predict therapeutic response. Disclosure: The presenting author, A.Vanderstichele, has no conflict of interest.